TAOK1 promotes filament formation in HR repair through phosphorylating USP7 - Tian-Chen Zhu; Zhang-Ping He; Shu-Ting Li; Lin Zheng; Xue-Yi Zheng; Xia-Lu Lan; Chun-Hua Qu; Run-Cong Nie; Chao Gu; Li-Ning Huang; Xiao-Xia Cai; Zhi-Cheng Xiang; et al. (Proceedings of the National Academy of Sciences, 2025)
Poly-ADP-ribose polymerase (PARP) inhibitors are vital therapeutic agents that exploit synthetic lethality, particularly effective in tumors with homologous recombination (HR) defects. However, broadening their clinical utility remains a significant challenge. In this study, we conducted a high-throughput kinase inhibitor screen to identify potential targets exhibiting synthetical lethality with PARP inhibitors. Our results show that thousand and one amino acid protein kinase 1 (TAOK1) plays a pivotal role in the DNA damage response by phosphorylating ubiquitin specific peptidase 7 (USP7), thereby promoting its enzymatic activity and preventing the ubiquitylation and subsequent degradation of RAD51, a crucial protein in the filament formation of HR repair. Notably, genetic depletion or pharmacological inhibition of TAOK1, as well as blocking peptide targeting the USP7 phosphorylation site, impaired USP7 function, leading to RAD51 degradation, disruption of HR repair, and increased tumor cell and sensitivity to PARP inhibition. This study highlights TAOK1 as a critical regulator of HR repair pathway in human cancer cells and presents a therapeutic strategy overcoming resistance to PARPi inhibitors. These findings support the potential clinical application of combining PARP inhibitors with TAOK1 inhibition or peptide treatment to improve therapeutic outcomes.